Development and validation of a questionnaire on teaching and learning in remote education (Educação e Pesquisa, 2022)
This article presents a questionnaire proposal to inquire about teaching and learning in remote education. The questionnaire consists of 6 dimensions, 38 indicators, and 2 open-ended questions. The dimensions pertain to instructional planning, teaching resources, assessment for learning, social interaction, and pedagogical support. The instrument was constructed through an iterative process according to criteria of coherence and relevance considering the literature on the subject. The questionnaire was validated by five expert trials with the same criteria for its construction. The instrument was applied to a non-probabilistic sample of 202 teachers at different levels of school education. The overall reliability of the questionnaire was 0.943, so it has a high consistency between the indicators and the construct. The factorial analysis performed on the questionnaire indicates that there are seven factors that explain 61.6% of the total variance. These results indicate that it is a valid and reliable tool to inquire about the teaching and learning process in remote education. It is concluded that this instrument is a proposal that collaborates with the elaboration of relevant research criteria to study this emerging issue.